Direct Synthesis of Disubstituted Trifluoromethylthiolated Alkenes - Fichez, Jeanne; Dupommier, Dorian; Besset, Tatiana (Synthesis, 2022)
In the field of organofluorine chemistry, the quest for emergent fluorinated groups is in high demand. In particular, the scientific community has shown special interest in the SCF3 residue thanks to its unique properties. Indeed, over the last decade, the SCF3 group has become a pivotal fluorinated moiety, as demonstrated by several SCF3-containing compounds of interest, and, related to that, the steadily increasing number of synthetic methods that are available to access such molecules. In this Short Review, the main advances made for the synthesis of trifluoromethylthiolated disubstituted alkenes will be discussed and highlighted.1 Introduction2 Trifluoromethylthiolation of Prefunctionalized Alkenes3 Direct C–H Trifluoromethylthiolation of Alkenes4 Trifluoromethylthiolation of Miscellaneous Derivatives5 Conclusion
Keywords: trifluoromethylthiolation; synthetic methodologies; organofluorine chemistry; disubstituted olefins; homogeneous catalysis; transition-metal-free reactions